Planetary status. - Wong, Yu Ling. (2010)
PLANETARY STATUS is an animation short inspired by the International Astronomical Union (IAU)’s announcement which states that Pluto is no longer being classified as a planet. It revolves around the journey of a frantic scientist, Pluto, who desires to be one of the newly enlisted members recruited by Lord Solaris into the exclusive Solaris Club. Pluto tries all his means to get to Lord Solaris’ Palace; unfortunately he is delayed with much hindrance. This project tries to play on the fact that Pluto (the planet) was excluded from the Solar System planet status. The pun attempts to offer the “back story”, explaining this alteration of fact. It reminded us that even a fact could change over time.